2010
DOI: 10.1103/physrevb.82.165121
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer in FeOCl intercalation compounds and its pressure dependence: An x-ray spectroscopic study

Abstract: We present a study of charge transfer in Na-intercalated FeOCl and polyaniline-intercalated FeOCl using high-resolution x-ray absorption spectroscopy and resonant x-ray emission spectroscopy at the Fe-K edge. By comparing the experimental data with ab-initio simulations, we are able to unambiguously distinguish the spectral changes which appear due to intercalation into those of electronic origin and those of structural origin. For both systems, we find that about 25% of the Fe sites are reduced to Fe 2+ via c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
(73 reference statements)
1
20
0
Order By: Relevance
“…The decomposition of H 2 O 2 over Fe/SBA‐15‐MF followed a two‐step pattern with respect to H 2 O 2 concentration, being different with previous studies . Within the van der Waals layers, an electron transfer process became feasible . We assume that an active complex was formed immediately when FeOCl interacted with H 2 O 2 , denoted as FH.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The decomposition of H 2 O 2 over Fe/SBA‐15‐MF followed a two‐step pattern with respect to H 2 O 2 concentration, being different with previous studies . Within the van der Waals layers, an electron transfer process became feasible . We assume that an active complex was formed immediately when FeOCl interacted with H 2 O 2 , denoted as FH.…”
Section: Resultsmentioning
confidence: 72%
“…Within the so‐called “Van de Waals layer,” charge transfer between organic molecules and ferric ion can occur readily (Eq. ) . We assume that the ferrous ion may trigger the Fenton reaction (Eq.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was shown that the charge transfer in polyaniline-intercalated FeOCl can be enhanced through the application of external pressure. 27 A pressure-induced increase in conductivity in the FeOCl intercalated compounds could be of interest for their application as cathode materials. Although such intercalated systems are intensively studied, there is no information on the behavior of pure FeOCl under high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Among layered compounds with a van der Waals gap metal oxyhalides have been widely used as host lattices. [21][22][23][24][25][26][27] Intercalation enables confining guest molecules or polymer chains in a well-defined environment. The resulting intercalation hybrids often exhibit novel magnetic and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…During the aniline treatment, FeOCl acted as the host and the electron acceptor, the aniline molecules intercalated into the interlayers of FeOCl were oxidatively polymerized by the Fe 3+ (Fe−Cl) in the FeOCl. Meanwhile, part of the Fe 3+ sites in the FeOCl crystal was reduced to the Fe 2+ state, which was evidenced by the Mossbauer spectroscopy and X‐ray spectroscopic analysis . Upon further treatment, the peak at 6.4° became stronger and the peak at 11.2° was further weakened, indicating the intercalation reaction was proceeded and more FeOCl/PANI phase was formed.…”
Section: Resultsmentioning
confidence: 97%